2021
DOI: 10.1177/01455613211048998
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and anosmia: The story so far

Abstract: Objectives The pandemic has affected over 182 million coronavirus disease 2019 (COVID-19) cases worldwide. Accumulated evidence indicates that anosmia is one of the significant characteristics of COVID-19 with a high prevalence. However, many aspects of COVID-19-induced anosmia are still far from being fully understood. The purpose of this review is to summarize recent developments in COVID-19-induced anosmia to increase awareness of the condition. Methods A literature search was carried out using the PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 76 publications
(148 reference statements)
0
19
0
3
Order By: Relevance
“…COVID-19 predominantly affects the respiratory system of the human body, but it can also cause harm to the central nervous, cardiovascular, gastrointestinal, hepatobiliary, and renal systems [3] . In addition, COVID-19 might induce otolaryngology diseases such as anosmia and sudden sensorineural hearing loss ( HL ) [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 predominantly affects the respiratory system of the human body, but it can also cause harm to the central nervous, cardiovascular, gastrointestinal, hepatobiliary, and renal systems [3] . In addition, COVID-19 might induce otolaryngology diseases such as anosmia and sudden sensorineural hearing loss ( HL ) [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 infects human cells through the angiotensin-converting enzyme 2 ( ACE2 ), activating transmembrane serine protease 2 ( TMPRSS2 ), hence enhancing viral uptake [5] . The SARS-CoV-2 virus may infect both the central and peripheral nerve systems, resulting in neurological disorders [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Don et al ( 16 ) revealed that SO for tympanostomy tube monitoring is workable, allowing otolaryngologists to remotely track children's tympanostomy tubes and providing greater parental satisfaction. With high severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral load in the nose and throat and anosmia as one feature of COVID-19, otolaryngology is a high-risk department for COVID-19 ( 9 , 23 , 24 ). As a result, several studies used SO for telemedicine services during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a structural study of the OB in olfactory dysfunction demonstrated a layer-specific neuronal loss in the glomerular layer [ 46 ], and degenerative changes in OB neurons has been found in AD [ 47 ]; the post-mortem high-resolution MRI of the brains affected by SARS-CoV-2 and histopathological examination demonstrated microvascular changes in OB [ 48 ]. Therefore, future studies on OB in a normal state and pathology will include investigation of the both gross- and micromorphology.…”
Section: Discussionmentioning
confidence: 99%